Development of Android-Based Chemistry Virtual Laboratory Media on Acid-Base Materials for 11th Grade High School Students - Firda Elfiana Muslim; Ivan Ashif Ardhana (Universitas Pendidikan Mandalika, 2023)
This study aimed to develop an Android-based virtual laboratory media for chemistry, assess its validity, and determine students' responses to it. The research methodology employed was research and development (R&D) with the 4D development model (Four D Models) according to Thiagarajan, which comprises four stages: define, design, develop, and disseminate. The study was carried out until the development stage. The research instruments used included interview guides, validation sheets, and questionnaires. The media products developed were validated by material and media expert validators consisting of two chemistry lecturers and one chemistry teacher. Limited trials were conducted with a total of 32 11th grade students from Mathematics and Science (MIPA) 3 class at State Islamic Senior High School (MAN) Blitar City. Data analysis techniques involved both qualitative and quantitative methods. The results indicate that the validation scores from the material and media experts were very valid, with an average percentage score of 98% and 95%, respectively. The student's responses to the limited trials were also very good, with an average percentage score of 88%. Overall, the study demonstrated the potential of the developed Android-based virtual laboratory media for chemistry education.